COVID-19 Vaccines May Not Prevent Nasal SARS-CoV-2 Infection and Asymptomatic Transmission. (February 2021) - Bleier, Benjamin S.; Ramanathan, Murugappan; Lane, Andrew P.
Current COVID-19 vaccine candidates are administered by injection and designed to produce an IgG response, preventing viremia and the COVID-19 syndrome. However, systemic respiratory vaccines generally provide limited protection against viral replication and shedding within the airway, as this requires a local mucosal secretory IgA response. Indeed, preclinical studies of adenovirus and mRNA candidate vaccines demonstrated persistent virus in nasal swabs despite preventing COVID-19. This suggests that systemically vaccinated patients, while asymptomatic, may still be become infected and transmit live virus from the upper airway. COVID-19 is known to spread through respiratory droplets and aerosols. Furthermore, significant evidence has shown that many clinic and surgical endonasal procedures are aerosol generating. Until further knowledge is acquired regarding mucosal immunity following systemic vaccination, otolaryngology providers should maintain precautions against viral transmission to protect the proportion of persistently vulnerable patients who exhibit subtotal vaccine efficacy or waning immunity or who defer vaccination.